Tingkat Adopsi Petani Terhadap Sistem Tanam Jajar Legowo (Studi Kasus Di Kecamatan Batang Anai Kabupaten Padang Pariaman) - Sandra Dewi; Rahmat Syahni; Zulvera (Jurnal Niara, 2023)
This study examines the factors that influence the level of farmer adoption of the jajar legowo planting system in Kecamatan Batang Anai, Kabupaten Padang Pariaman. This research was conducted from April to June 2022 on 8 farmer groups that implemented the jajar legowo planting system in 2021. The objectives of this study were: to analyze the adoption rate of farmers towards the jajar legowo planting system in Kecamatan Batang Anai Kabupaten Padang Pariaman. This study uses a survey method with a quantitative approach in collecting data from a population of farmers who apply the jajar legowo planting system in 2021 with a sample of 112 farmers. The analytical tools used for this study were obtained from the calculation of the total score divided by the number of questions. Then the interval class was determined with the following details: (1) Not applying or low (15-35), (2) Partial or moderate (36-56), and (3) Applying completely or high (˃56). The results showed that the level of farmer adoption of the jajar legowo planting system in Kecamatan Batang Anai Kabupaten Padang Pariaman was assessed from the level of technical application of cultivation of the jajar legowo planting system recommended by the Center for the Study of Agricultural Technology in the medium category with 36-56 intervals which included the following activities: processing land, making plant rows, planting, fertilizing, weeding and controlling Plant Pest Organisms. Conclusions and recommendations From this research, education, cosmopolitan as an indicator of farmer characteristics variables need to be improved, one of which is by increasing farmers' knowledge through training and technical guidance and intensity of extension meetings with farmers, implementing group or individual extension methods and increasing farmers' ability to utilize and access information media